Influence of food safety knowledge, attitudes and practices of processors on microbiological quality of commercially produced traditional fermented cereal beverages, a case of Obushera in Kampala - Byakika, Stellah; Muzira Mukisa, Ivan; Byenkya Byaruhanga, Yusuf; Male, Denis; Muyanja, Charles (Food Control, 2019)
Traditionally, fermented foods were only consumed in regions of their origins but owing to increasing demand, some are finding their way into foreign markets. The challenge though, is the generally uncontrolled nature of the fermentations which raises safety concerns. This paper highlights the food safety challenges associated with traditional fermented foods with a special focus on commercially produced and packaged Obushera, a Ugandan traditional fermented cereal beverage. Microbial counts, titratable acidity (TA) and pH of Obushera samples (n=59) were determined. Food safety knowledge, attitudes and practices (KAP) of processors (n=47) were also evaluated. About 50% of samples did not conform to safety requirements. Obushera had 0.0–7.3 log cfu/mL total and thermo-tolerant coliforms, 0.0–6.2 log cfu/mL E. coli and 0.0–8.1 log cfu/mL Staphylococcus spp. Flour samples had 3.7–7.3 log cfu/g total coliforms, 3.2–7.1 log cfu/g thermo-tolerant coliforms, 1.0–4.9 log cfu/g E. coli and 2.4–7.3 log cfu/g Staphylococcus spp. Salmonella spp was not detected. Obushera (56 out of 59 samples) with pH≤4.0 and TA=0.1–3.1% had coliforms and Staphylococcus spp above the recommended minimum values. Scores showed that processors had fairly good knowledge (63.0 ± 2.3%) and attitudes (52.2 ± 3.0%) but poor practices (38.7 ± 2.4%). There was no correlation between the KAP and product quality. Therefore, processors should adopt better processing technologies that enhance food safety. There is also need for enforcement and regulation of food safety by concerned authorities. Trainings for processors should aim at positively changing their attitudes and causing them to adopt appropriate practices.
Keywords: Fermented foods; Obushera; Pathogens; Safety; Public health